Characterization of transesterification reactions by Mucoromycotina lipases in non-aqueous media - Kotogán, Alexandra; Kecskeméti, Anita; Szekeres, András; Papp, Tamás; Chandrasekaran, Muthusamy; Kadaikunnan, Shine; Alharbi, Naiyf S.; Vágvölgyi, Csaba; Takó, Miklós (Journal of molecular catalysis. B, Enzymatic, 2016)
[Display omitted] •Mucoromycotina lipases as transesterifying catalysts were studied in solvents.•Various aryl esters and alcohols were used for reaction characterization.•Steady conversion with maximum yields from 61.2 to 90.5% was obtained at 96h.•The biocatalysts displayed high tolerance to ethanol and non-polar solvents.•High initial affinities toward esters with C8 and C12 acids were detected. Transesterification properties of Rhizomucor, Rhizopus, Mucor, Umbelopsis and Mortierella crude lipases were investigated in water-free systems using an UV spectrophotometric method. Conversion of p-nitrophenyl palmitate (pNPP) with ethanol was characterized under various reaction conditions. Best conversion yields were generally obtained at 40°C in n-heptane, but temperature of 50°C and the solvents hexane and isooctane proved to be also useful. Then, crude lipases from five strains, namely Rhizomucor miehei NRRL 5282, Rhizopus oryzae NRRL 1526, Rhizopus stolonifer SZMC 13609, Mucor corticolus SZMC 12031 and Mortierella echinosphaera CBS 575.75 were selected for further kinetic studies and to evaluate the effect of the acyl acceptors and donors with various chain lengths on the reaction. In general, ethanol up to 4.25mol/L concentration enhanced the catalytic activities, and a steady conversion with maximum yields ranging from 61.2% to 90.5% was obtained at about 96h. Replacement of ethanol as the acyl acceptor with methanol, isopropanol, n-butanol or n-hexanol resulted in lower conversions when incubated with the same concentration. The selected crude lipases demonstrated high initial affinity toward the medium-chain aryl esters with C8 and C12 acids. Esterification of palmitic acid with ethanol showed much slower catalysis rates resulting in less specific activities than transesterification. The high stability in organic solvents makes the investigated crude enzymes promising candidates for further studies aiming at the application in organic synthesis processes.